(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
This scientific article delves into the critical role of gamification in primary school in teaching English, highlighting its impact on enhancing language acquisition, motivation, and overall learning experience. By examining various studies and educational practices, this paper elucidates the effectiveness of integrating games as a pedagogical tool to foster language skills in young learners. This article explores the diverse array of games used to teach English in primary schools, shedding light on how they contribute to linguistic development, motivation, and overall educational enrichment.